Long term effects of manual lymphatic drainage and active exercises on physical morbidities, lymphoscintigraphy parameters and lymphedema formation in patients operated due to breast cancer: A clinical trial - Oliveira, Mariana Maia Freire de; Gurgel, Maria Salete Costa; Amorim, Bárbara Juarez; Ramos, Celso Dario; Derchain, Sophie; Furlan-Santos, Natachie; dos Santos, César Cabello; Sarian, Luís Otávio (PLOS ONE, 2018)
Purpose evaluate whether manual lymphatic drainage (MLD) or active exercise (AE) is associated with shoulder range of motion (ROM), wound complication and changes in the lymphatic parameters after breast cancer (BC) surgery and whether these parameters have an association with lymphedema formation in the long run. Methods Clinical trial with 106 women undergoing radical BC surgery, in the Women’s Integrated Healthcare Center—University of Campinas. Women were matched for staging, age and body mass index and were allocated to performed AE or MLD, 2 weekly sessions during one month after surgery. The wound was evaluated 2 months after surgery. ROM, upper limb circumference measurement and upper limb lymphoscintigraphy were performed before surgery, and 2 and 30 months after surgery. Results The incidence of seroma, dehiscence and infection did not differ between groups. Both groups showed ROM deficit of flexion and abduction in the second month postoperative and partial recovery after 30 months. Cumulative incidence of lymphedema was 23.8% and did not differ between groups (p = 0.29). Concerning the lymphoscintigraphy parameters, there was a significant convergent trend between baseline degree uptake (p = 0.003) and velocity visualization of axillary lymph nodes (p = 0.001) with lymphedema formation. A reduced marker uptake before or after surgery predicted lymphedema formation in the long run (>2 years). None of the lymphoscintigraphy parameters were shown to be associated with the study group. Age ≤39 years was the factor with the greatest association with lymphedema (p = 0.009). In women with age ≤39 years, BMI >24Kg/m2 was significantly associated with lymphedema (p = 0.017). In women over 39 years old, women treated with MLD were at a significantly higher risk of developing lymphedema (p = 0.011). Conclusion Lymphatic abnormalities precede lymphedema formation in BC patients. In younger women, obesity seems to be the major player in lymphedema development and, in older women, improving muscle strength through AE can prevent lymphedema. In essence, MLD is as safe and effective as AE in rehabilitation after breast cancer surgery.